Mead and other fermented beverages - Pereira, A. P. (2017)
This chapter introduces the production of mead, a traditional alcoholic fermented beverage. It starts with an introduction to mead that includes historical aspects of production and a description of some styles and derivative products. Then, the raw material in mead production, the honey, is characterized in terms of its physicochemical composition and microbiota. Next, we focus on some aspects of mead production, such as the steps involved, the problems associated with the fermentation (the yeast inoculation and the nutrient supplementation of must), and the application of immobilized yeasts to the production. At the end is presented a detailed description of honey and fermentation-derived volatiles, the main contributors to mead aroma. Finally, we present an approach to the sensory evaluation of mead, an indispensable method to assess the beverage quality.